Evaluation of emotional excitation during standardized endotracheal intubation in simulated conditions - Marjanovic, Nicolas S. (Ann Intensive Care, 2018)
OBJECTIVE: To assess how stressful conditions in endotracheal intubation could induct emotional excitation in a population of acute care physicians. MATERIALS AND METHODS: Two situations were randomly tested: one in standard and easy intubation conditions the other under difficult conditions presumed to induce stress (monitoring alarms, manikin lying on the floor, difficult intubation). Emotional excitation was assessed using several physiological (cardiac patterns, electrodermal activity and eye-tracking) and psycho-cognitive patterns. Auto-evaluations of video recordings and mental workload were performed immediately after simulation. RESULTS: Significant physiological parameter modifications were observed under the stressful intubation conditions (SDNN 35 ± 15 vs. 42 ± 21; p = 0.035—AVNN 514 ± 94 vs. 548 ± 110; p < 0.0001). Emotional excitation was demonstrated to lead a higher mental workload (NASA-TLX = 39 ± 18 vs. 63 ± 15; p = 0.001), frustration and effort dimensions being its determinant components (p < 0.01). Video recording auto-evaluations depicted significant emotional excitation occurrence under the difficult conditions, with few differences according to the operator’s experience. CONCLUSION: This study highlights the fact that a stress condition during ETI on a simulation model leads to an important emotional excitation as compared to the neutral condition.